Lipoarabinomannan in Active and Passive Protection Against Tuberculosis - Correia-Neves, Margarida; Sundling, Christopher; Cooper, Andrea; Källenius, Gunilla (Frontiers in Immunology, 2019)
Glycolipids of the cell wall of Mycobacterium tuberculosis (Mtb) are important immunomodulators in tuberculosis. In particular lipoarabinomannan (LAM) has a profound effect on the innate immune response. LAM and its structural variants can be recognized by and activate human CD1b restricted T cells, and emerging evidence indicates that B cells and antibody against LAM can modulate the immune response to Mtb. Anti-LAM antibodies are induced during Mtb infection and after BCG vaccination, and monoclonal antibodies against LAM have been shown to confer protection by passive administration in mice and guinea pigs. In this review we describe the immune response against LAM and the potential use of the mannose-capped arabinan moiety of LAM in the construction of vaccine candidates against tuberculosis.